THE INFLUENCE OF ANIMATED VIDEOS ON ADOLESCENTS' KNOWLEDGE AND ATTITUDES ABOUT PREMARITAL SEX AT ISTIQOMAH MUHAMMADIYAH 4 VOCATIONAL SCHOOL, SAMARINDA - Salma Khairani Putri; Chandra Sulistyorini; Ida Hayati; Dwi Ida Puspitasari (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Premarital sex is a behavior in which a person engages in sexual intercourse with the opposite sex without coercion and with or without a romantic relationship. Adolescents' attitudes toward premarital sexual activity are influenced by various factors, including knowledge, culture, mass media, personal experiences, the role of educational and religious institutions, and the individual's own emotional state. Audiovisual media is an effective medium for conveying messages about early sex education to adolescents. This type of media is an appropriate learning strategy for adolescents because it is engaging and engaging. To analyze the effect of animated video-based health education on increasing adolescents' knowledge and attitudes regarding Premarital Sex. This study used a Quasi-experimental design with a One Group Pre-test and Post-test. The study was conducted in September 2025. The population was all eleventh-grade students of SMK Istiqomah Muhammadiyah 4 Samarinda. The sample consisted of 99 people. The type and collection of data were primary data using a questionnaire. The statistical test used was the Wilcoxon Test. There is an influence between knowledge before and after being given health education using animated videos with a p value <0.001. There is an influence of respondents' knowledge and attitudes after being given health education using animated video media on adolescents' knowledge and attitudes about Premarital Sex at SMK Istiqomah Muhammadiyah 4 Samarinda.